Dose Negative Social Impact Vividly Influence On Tourism Sector In Panama Region Of Sri lanka? - Nisthar, A.; Vijayakumar, S. (University of jaffna, 2018)
This study aims to analyze the factors of negative social impacts of tourism and their relationship with its entire effects on the local community in Panama region of Sri Lanka by using quantitative method. The questionnaire designed to collect the qualitative data is in the format of Five Likert Scale. The data have been collected in year 2018/2019. Factor Analysis, Multi-co-linearity Statistics, Multiple Regression, and Analysis of Residuals are the techniques used in this study to achieve the objective of this study by using SPSS v.20. The Total Effect of tourism is used as the dependent variable in the model of this study. Use of Drugs & Changes in Food Patterns, Worry about Discipline of Children, Exploitation of Children, and Malpractices of Women are the four independent variables representing negative social impacts of tourism extracted from the factor analysis. There are direct relationships between all the independent variables and the dependent variable. All the negative social impacts of tourism are confirmed by the direction, the significance, and strength of positive linear relationship of the dependent and the independent variables. The effects of Worry about Discipline of Children are perceived by the local community preferably higher among the negative social factors.
Keywords: Negative Social Impacts; Children; Panama; Sri Lanka; Local Community; Tourism